2021
DOI: 10.1212/wnl.0000000000012997
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation and Protein Markers of Chronic Inflammation and Their Associations With Brain and Cognitive Aging

Abstract: Objective:To investigate chronic inflammation in relation cognitive ageing by comparison of an epigenetic and serum biomarker of C-Reactive Protein and their associations with neuroimaging and cognitive outcomes.Methods:At baseline, participants (N = 521) were cognitively normal, around 73 years of age (M = 72.4, SD = 0.716), and had inflammation, vascular risk (cardiovascular disease history, hypertension, diabetes, smoking, alcohol consumption and BMI) and neuroimaging (structural and diffusion MRI) data ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 55 publications
2
49
0
Order By: Relevance
“…Many of the 191 proteins identified in the protein PheWAS were part of inflammatory clusters with shared functions in acute phase response, complement cascade activity, innate immune activity and cytokine pathways. Tissue expression analyses suggested that a large proportion of the 191 protein markers were not expressed in the brain; this supports work suggesting that sustained peripheral inflammation influences general brain health 31 , 32 and accelerates cognitive decline 17 , 33 35 . However, a subset of proteins were expressed in the central nervous system.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Many of the 191 proteins identified in the protein PheWAS were part of inflammatory clusters with shared functions in acute phase response, complement cascade activity, innate immune activity and cytokine pathways. Tissue expression analyses suggested that a large proportion of the 191 protein markers were not expressed in the brain; this supports work suggesting that sustained peripheral inflammation influences general brain health 31 , 32 and accelerates cognitive decline 17 , 33 35 . However, a subset of proteins were expressed in the central nervous system.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, DNAm accounts for inter-individual variability in circulating protein levels [14][15][16] . Recently, through integration of DNAm and protein data, we have shown that epigenetic scores for plasma protein levels-known as EpiScores-associate with brain morphology and cognitive ageing markers 17 and predict the onset of neurological diseases 18 . These studies highlight that while datasets that allow for integration of proteomic, epigenetic and phenotypic information are rarely-available, they hold potential to advance risk stratification.…”
mentioning
confidence: 99%
“…CRP DNAm scores associated with more brain regions and with larger effect sizes than serum CRP, in the context of depression (36). Further, CRP DNAm scores were also better predictors of cognition than serum measures of CRP (35). Here, we found weak associations between CRP DNAm scores derived at birth and total number of PEs.…”
Section: Discussionmentioning
confidence: 93%
“…We therefore investigated novel epigenetic and genetic biomarkers of inflammation, which reflect a longer-term, more stable inflammatory exposure. Other studies, including our own investigating adult population cohorts, have highlighted the importance of researching DNAm markers of inflammation over serum-based markers (12, 35, 36). CRP DNAm scores associated with more brain regions and with larger effect sizes than serum CRP, in the context of depression (36).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that systemic inflammatory markers such as C-reactive protein (CRP) are associated with poorer cognitive functioning in older adults and in people with physical or mental health conditions (Misiak et al, 2018; Morrens et al, 2022; Sartori et al, 2012). Observational studies in the general population have also reported associations between inflammatory markers, such as CRP, Interleukin-6 (IL-6) and Glycoprotein acetyls (GlycA), and poorer general and domain-specific cognition (Conole et al, 2021; Kokosi et al, 2021; Mac Giollabhui et al, 2021; Shields et al, 2021; van der Lee et al, 2018); although improved cognition has also been reported (Milton et al, 2021). Regarding the human experimental literature, the effect of acute inflammatory challenges (endotoxin and vaccines) on hot (e.g., emotion recognition) and cold (e.g., attention, memory) cognitive domains have yielded inconsistent findings (Balter et al, 2018; Bollen et al, 2017; Brydon et al, 2008; Handke et al, 2020; Harrison et al, 2014).…”
Section: Introductionmentioning
confidence: 99%